Literature Review : Perkembangan Pengobatan Kemoterapi Kanker Payudara - Yuliana, Dewi; Wulan, Wulan (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Breast cancer is a condition where cells lose control and normal mechanisms, resulting in abnormal, fast and uncontrolled cell growth that occurs in the breast. Breast cancer is the most feared disease by women. One of the treatments is chemotherapy. The purpose of this study is to find out how the development of breast cancer chemotherapy treatment. As for the research method, this research uses literature review, in the search for literature sourced from 2 databases (Pubmed and Google Scholar) using keywords according to the theme. Where the results obtained show that chemotherapy treatment for breast cancer has developed where it has been found that monoclonal antibody therapy and gene therapy have been proven to increase disease-free expectations in breast cancer patients.